Letter - Winstanley, E.
030-0016-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. 87 Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. Our reference EXPORT 1733 ST/HP. 21st October, 1938. Your reference The Trades Union Congress, Transport House, Smith Square, LONDON SW. 1. Dear Sirs, We confirm our telephonic conversation this morning respecting the goods we have on order on your account for shipment to Spain. As desired we are cancelling the item for Sewing Machine Needles, and are placing into work an order for 75-lbs of Beacon Knitting Wool 4 ply. Yours faithfully, E. Winstanley Export Department. 292/946/30/16